2017
DOI: 10.5588/ijtld.16.0702
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the Xpert® MTB/RIF cycle threshold level to predict smear positivity: a meta-analysis

Abstract: Xpert CT values and smear status were strongly associated. However, diagnostic accuracy at set cut-off CT values of 27.7 or 31.8 would not replace smear microscopy. How CT values compare with smear microscopy in predicting infectiousness remains to be seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 40 publications
3
27
0
5
Order By: Relevance
“…These are also presented according to different CT cut-offs between 25 and 30 in Table 5 and Supplementary Table S4 . Cut-offs of 31.8 and 27.7 (sensitivity of 95%, specificity of 35% and sensitivity 85%, specificity 67%) identified by the recent meta-analysis of C T predictors of smear positivity 20 , resulted in sensitivity of 98.8%, specificity 22.0% with a cut-off of 31.8 and sensitivity of 94.2% and specificity of 58.3% in this study.
Figure 2 ROC curve analysis showing sensitivity for differing mean cycle threshold (C T ) – (average of positive Xpert MTB/RIF probes) values as a test for smear positivity.
…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…These are also presented according to different CT cut-offs between 25 and 30 in Table 5 and Supplementary Table S4 . Cut-offs of 31.8 and 27.7 (sensitivity of 95%, specificity of 35% and sensitivity 85%, specificity 67%) identified by the recent meta-analysis of C T predictors of smear positivity 20 , resulted in sensitivity of 98.8%, specificity 22.0% with a cut-off of 31.8 and sensitivity of 94.2% and specificity of 58.3% in this study.
Figure 2 ROC curve analysis showing sensitivity for differing mean cycle threshold (C T ) – (average of positive Xpert MTB/RIF probes) values as a test for smear positivity.
…”
Section: Resultssupporting
confidence: 48%
“…demonstrated that the correlation of TTP and C T is less strong among HIV positive individuals comparted to HIV negative individuals 18 . A recent meta-analysis identified cut-of C T values of 27.7 and 31.8 to predict smear positivity with 85% and 95% sensitivity respectively 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have reported on the correlation between the semi-quantitative results of Xpert and smear microscopy [35]. This positive correlation made Xpert semi-quantitative results useful to estimate patients' infectious potential and to guide airborne isolation strategies when integrated with other clinical features in smear independent algorithms [36e38] (Fig.…”
Section: Correlation Between the Semi-quantitative Results Of Ultra Anmentioning
confidence: 99%
“…The cycle threshold value (C T ) is the number of PCR cycles after which Xpert MTB/RIF probes successfully detect M tuberculosis DNA in a given sample. Xpert MTB/RIF C T values are strongly correlated with AFB smear status ( Lange 2017 ). The lower sensitivity of Xpert MTB/RIF in individuals with AFB smear‐negative PTB is related to the lower bacillary burden and higher associated C T value compared to individuals with AFB smear‐positive PTB.…”
Section: Discussionmentioning
confidence: 99%
“…The lower sensitivity of Xpert MTB/RIF in individuals with AFB smear‐negative PTB is related to the lower bacillary burden and higher associated C T value compared to individuals with AFB smear‐positive PTB. Individuals with PTB and HIV co‐infection are more likely to have smear‐negative tuberculosis, which implies a lower bacillary burden and higher mean C T values on Xpert testing ( Beynon 2018 ; Lange 2017 ), and this is the likely mechanism for the lower sensitivity of Xpert MTB/RIF for the diagnosis of tuberculosis in people living with HIV.…”
Section: Discussionmentioning
confidence: 99%